Cerebral CTA with Low Tube Voltage and Low Contrast Material Volume for Detection of Intracranial Aneurysms - Ni, Q.Q. (AJNR Am J Neuroradiol, 2016)
BACKGROUND AND PURPOSE: Multidetector row CTA has become the primary imaging technique for detecting intracranial aneurysms. Technical progress enables the use of cerebral CTA with lower radiation doses and contrast media. We evaluated the diagnostic accuracy of 80-kV(peak) cerebral CTA with 30 mL of contrast agent for detecting intracranial aneurysms. MATERIALS AND METHODS: Two hundred four patients were randomly divided into 2 groups. Patients in group A (n = 102) underwent 80-kVp CTA with 30 mL of contrast agent, while patients in group B (n = 102) underwent conventional CTA (120 kVp, 60 mL of contrast agent). All patients underwent DSA. Image quality, diagnostic accuracy, and radiation dose between the 2 groups were compared. RESULTS: Diagnostic image quality was obtained in 100 and 99 patients in groups A and B, respectively (P = .65). With DSA as reference standard, diagnostic accuracy on a per-aneurysm basis was 89.9% for group A and 93.9% for group B. For evaluating smaller aneurysms (<3 mm), the diagnostic accuracy of groups A and B was 86.3% and 90.8%, respectively. There was no difference in diagnostic accuracy between each CTA group and DSA (all, P > .05) or between the 2 CTA groups (all, P > .05). The effective dose in group A was reduced by 72.7% compared with group B. CONCLUSIONS: In detecting intracranial aneurysms with substantial radiation dose and contrast agent reduction, 80-kVp/30-mL contrast CTA provides the same diagnostic accuracy as conventional CTA.